DISTRIBUTION OF MICROORGANISMS BASED ON THE DIVERSITY OF AIRBORNE BACTERIA AND ENDOTOXIN CONCENTRATIONS IN THE CIBUBUR AND THE JAKARTA NATIONAL MONUMENT AREA - Khoerunnisa, Sonia
DKI Jakarta considered as cities with the worst air quality in the world. The reported index value is related to the concentration of particulate matter (PM) both PM2.5 and PM10. The study of the bacterial abundance and endotoxin concentration in Jakarta's air is very important, but has not been done much. Air with high concentrations of bioaerosols, might contain bacteria, viruses, fungi, and allergens, that has a negative impact on human health. This study aims to determine the effect of bacterial abundance and diversity, endotoxin concentration, physical factors, and their distribution in the air from Cibubur and the National Monument. Air sampling was carried out at the beginning of the rainy season at two locations at the gate of the Cibubur-1 Toll and the National Monument during the day and at night. Physical parameters measured using an automatic weather station (AWS) including temperature, humidity, equilibrium moisture curve (EMC), heat index¸ wind direction, and wind speed. The abundance and diversity of bacteria was observed by the total plate count method using a culture dependent approach. Air sampling was carried out for 4 hours during the day and night, with a final volume of 1.74 CFM. The bacteria obtained were then cultured using Nutrient Agar (NA), Tryptic Soy Agar (TSA), and Luria Bertani (LB). Endotoxin measurement was carried out using the thermo scientific Pierce LAL chromogenic endotoxin quantitation kit. Data analysis using the principal component analysis (PCA) method allows the identification of microclimate factors of the sample with 95% accuracy. Furthermore, correlation analysis was done by Pearson Correlation method. The abundance of bacteria from Cibubur air sample culture was 3.69 × 107 during the day and 1.12 × 107 at night; while the bacteria from air sample of the Jakarta National Monument during the day was 3.56 × 107 and at night was 3.43 × 107. The diversity of bacteria in the Cibubur air sample was classified as a moderate diversity group (H': 1.26; 1.45) with an even distribution of isolates (>0.75), while the National Monument air sample was classified as a low diversity group (H': 0.45; 1.06) with a lower evenness distribution (<0.75). The highest concentration of endotoxin was found in the Cibubur sample at night of 36.5 EU/m3 while the concentration in other samples was less than 30 EU/m3. The abundance of air microbes is influenced by temperature and humidity while the endotoxin concentration is strongly influenced by temperature, humidity, and wind direction. The distribution of microbes can be viewed from the direction of gusts and wind speed. During the day, air microbes around the National Monument (1.9 m/s) and Cibubur (0.2 m/s) are scattered towards the south of Jakarta, following the wind direction. Although the wind speed at the National Monument is much higher, the area is surrounded by trees and tall buildings, so the spread of microbes will be slower due to air turbulence around Monas. At night, the wind from the National Monument blows towards the southwest (0.4 m/s) and south-southwest (0.6 m/s), affecting the movement of the Cibubur wind, while the direction of the Cibubur wind blows towards the city of Depok. At the time of sampling in Cibubur at night there were extreme environmental changes caused by the rain so that viable microbes in the air became low. This research proves that environmental parameters greatly affect the abundance, diversity, and distribution of airborne bacteria in DKI Jakarta.